Time evolution of active caspase‐3 labelling after in vivo exposure to UVR‐300 nm. (3rd April 2014) - Talebizadeh, Nooshin; Yu, Zhaohua; Kronschläger, Martin; Söderberg, Per
Abstract Purpose To determine the time evolution of active caspase‐3 protein expression in albino rat lens after in vivo exposure to low‐dose UVR‐300 nm, as detected by immunofluorescence. Methods Forty Sprague‐Dawley rats were unilaterally exposed in vivo to 1 kJ/m2 UVR‐300 nm for 15 min. At 0.5, 8, 16 and 24 hr after the UVR exposure, the exposed and contralateral nonexposed lenses were removed and processed for immunohistochemistry. Three mid‐sagittal sections from each lens were stained. The cells labelled for active caspase‐3 in each section of both the exposed and nonexposed lenses were counted and recorded three times. The difference of the proportion of labelling between the exposed and contralateral nonexposed lenses within each animal was calculated. The differences of active caspase‐3 labelling at four different time‐points after exposure were used to determine the time evolution of active caspase‐3 expression. Results Caspase‐3 expression was higher in the exposed than in contralateral nonexposed lenses. The mean difference between the exposed and contralateral nonexposed lenses, including all lenses from all time intervals, was 0.12 ± 0.01 (= CI 95%). The mean differences between the exposed and contralateral nonexposed lenses were 0.11 ± 0.02, 0.13 ± 0.02, 0.14 ± 0.01 and 0.09 ± 0.03 (= CI 95%) for the 0.5‐, 8‐, 16‐ and 24‐hr time groups, respectively. The orthogonal comparison showed no difference in the expression of active caspase‐3 between the 0.5‐ and the 24‐hr groups (Test statistic 1.50, F1, 36 = 4.11, p < 0.05) or between the 8‐ and the 16‐hr groups (test statistic 0.05, F1, 36 = 4.11, p < 0.05). There was a difference when comparing the 0.5‐ and 24‐hr groups to the 8‐ and 16‐hr groups (test statistic 7.01, F1, 36 = 4.11, p < 0.05). Conclusion The expression of active caspase‐3 in the lens epithelium increases after UVR exposure. There is a peak of expression approximately 16 hr after the exposure.